Theological Approach and Understanding of Religions: Jean Denielou and Raimundo Panikkar: A study in Contrast - Kuttianimattathil S.D.B., Jose (Journal of Dharma, 1988)
Dominic Veliath, Theological Approach and Understanding of Religions: Jean Denielou and Raimundo Panikkar: A study in Contrast. Kristu Jyoti Publications, Bangalore 560036, India 1988, pp. xiv+407, Price Rs. 100/- $ 22.00.